الكلمات الملايوية ذات أصل عربي في قاموس دايا والاستفادة منها في تعليم اللغة العربية للملايويين المبتدئين - Wilda Elfitria; Husnul Khatimah (Rayah Al-Islam, 2019)
ABSTRACT The arrival of Islam to the Malay world affected the live of Malay muslims in various aspects, especially in linguistic. Unfortunately, most of Malay people do not know and they do not aware of these words in their language which they communicate everyday. Therefore, this research was based on the analytical descriptive methods that aims to detect Arabic words which have become a part of Malay in the "Kamus Daya" which starts with letter N, and to know the changes that occur after entering into Malay in terms of phonology and semantics, and how it implies in teaching Arabic for beginners. This research has proven that the existence of Arabic words in Malay in the Daya Dictionary consisked of fifty-seven words, and from these words we can group them into four groups, the first Malay words that do not change their meaning from the Arabic meaning, the second words that extend in their meaning, the third words that narrow in their meaning, and the fourth are words that change completely their meaning. this research presents an example of Malay vocabulary comes from the Arabic contained in the conversation, readings and exercise, for example Arabic learning for beginners from Malay learners.